Broadband internet availability and establishments' employment growth in Germany: evidence from instrumental variables estimations - Bastian Stockinger (Journal for Labour Market Research, 2019)
This study investigates the effect of broadband internet availability on German establishments' employment growth. The database used is a random sample of business establishments, augmented by the local availability of broadband. The observation period is 2005-2010, when broadband was introduced in rural regions of Western Germany and in large parts of Eastern Germany. For the Western German subsample, technical frictions in broadband rollout are exploited to obtain exogenous variation in broadband availability. The findings indicate a negative (albeit not very robust) employment growth effect of broadband availability for Western German manufacturers, and a robustly positive effect for Western German service establishments, including most knowledge-intensive industries. For Eastern Germany, a similar identification strategy is potentially available, but turns out invalid in this particular setting. An alternative identification approach (a long difference model) indicates positive employment growth effects in both sectors for Eastern Germany. Overall, the findings suggest that broadband expansion has helped create jobs in firms which use broadband intensely.
Keywords: J23; O33; R23; 330; Labor demand; Employment growth; Broadband internet; Technological change; Regional labor markets